Peningkatan Literasi Keuangan melalui Perencanaan Dana Pendidikan Anak - Hani Damayanti Aprilia; Ita Prihantika; Jeni Wulandari; Damayanti Damayanti (Jurnal Pengabdian Dharma Wacana, 2022)
This activity aims to provide knowledge, understanding, and skills to the community through training in planning for children's education funds as an effort to increase financial literacy. The method used is by training and practice. Evaluation of the training, among others, by looking at: (1) Participants' understanding of the material provided based on the results of the participants' pre-test and post-test evaluations; (2) the enthusiasm/response of participants in participating in the activities; (3) the ability of participants in practice; (4) Clarity of the speaker in delivering the material. The long-term target to be achieved in this activity is to make the community through PKK cadres able to manage family finances so that they can plan and prepare children's education funds in the future. Overall, the average score of participants before the socialization activities was carried out was 24.67 and increased to 71.67 after the training activities were carried out. An average increase of 47 points. The highest pre test score is 30 and the lowest score is 10, while for the post test session the highest score is 80 and the lowest score is 50. Based on these results, it can be concluded that this service activity is able to have a positive cognitive impact on knowledge about how to prepare children's education funds. . Meanwhile, in terms of affective awareness, willingness, and ability of participants in implementing family financial management so that they can plan and prepare funds for children's education in the future.